ANALYSIS OF LEARNING NEEDS IN THE COURSE NETWORK BASICS OF SPORT EDUCATION DURING PANDEMIC COVID-19 - Khairul Usman (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna Medan, 2020)
The purpose of this study was to determine the needs analysis for online learning in the Basics of Sports Education course during the Covid-19 Pandemic. The application of online lectures on the basics of sports education for all 9 classes using the Online System (Sipda) accompanied by google classroom and whatsapp gorup media as written communication. The use of google meet and zoom applications as direct communication via video conference. The method used is descriptive qualitative with a case study design. The instrument used is the learning activity rubric, which is to review the google classroom lecture tools and face-to-face lectures via zoom. The validity of the applied data is through a process of credibility and dependability. Based on data collection, it is obtained that the percentage of interaction via video conference is higher than the use of other media. Information is corroborated by students who are very willing to apply the lecture system which is shown by 100% or all students submit assignments and 98% submit on time. The assignment is then adjusted to the KKNI curriculum, namely by uploading the assignment on YouTube and other social media with reference to books or journals. The conclusions obtained from the results of the needs analysis study found based on the lecture process on the basics of sports education are 1) lectures are applied by direct communication (via video conference) or through direct instruction from the lecturer, 2) it is necessary to assign assignments with video students practice the subject material (uploaded on youtube); 3) Reflection at each meeting as a measure of the success of the meeting; 4) provide reinforcement of the weaknesses experienced by students, namely regulations that have tolerance for students who have network difficulties.